Analysis and Modelling of the Measurable, Electrical HF-Quantities of an IPMSM and their Dependencies - Hittinger, Christoph; Graus, Johannes; Hahn, Ingo; Wagner, Johannes (Electrical Machines and Systems (ICEMS), 2016 19th International Conference on, 2016)

A New Method for the Estimation of the Influence of Stator Saturation on the Differential Inductances - Graus, Johannes; Hahn, Ingo (IEMDC 2013, 2013)
For sensorless position detection of permanent magnet synchronous machines at very low speed and standstill, signal injection methods are commonly used. As a prerequisite these so called saliency-tracking methods require a differential magnetic anisotropy of the machine, which is both position and load dependent and thus varying during operation. So the performance of sensorless operation strongly depends on the machine design. To investigate the influence of the stator saturation on the differential inductances of a machine with concentrated winding, a model based on a magnetic equivalent circuit is used. The results show that for some angles of the current vector the inductances do not vanish even for high currents. To explain this phenomenon a new method for the qualitative estimation of both the stator tooth and yoke saturation is derived that shows very good agreement with the simulation results. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.anewme
Keywords: concentrated winding; cross saturation; differential magnetic anisotropy; magnetic equivalent circuit; permanent magnet synchronous machine; sensorless position detection

Comparison of the Resistance- and Inductance-Based Saliency of a PMSM due to a Short-Circuited Rotor Winding - Graus, Johannes; Rambetius, Alexander; Hahn, Ingo (International Power Electronics Conference - ECCE Asia (IPEC 2014), 2014)
Sensorless position estimation based on signal-injection methods always requires a resistance- or inductance-based anisotropy. Therefore, a short-circuited electrical winding can be attached on the rotor. As will be derived in this paper, this method leads to both a resistance- and inductance-based saliency. By an experimental test setup, both saliencies are analyzed and compared towards their accuracy and frequency-dependence. Thereby, for the resistance-based saliency a characteristic behavior is found that can be explained by the interaction between the rotor winding and the eddy current effect. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.compar
Keywords: Eddy currents; interior permanent magnet (IPM) motor; ringed pole; sensorless control

Improved Accuracy of Sensorless Position Estimation by Combining Resistance- and Inductance-Based Saliency Tracking - Graus, Johannes; Hahn, Ingo (IECON 2015, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IE.LEEAS.improv

Influence of Partly Closed Slots on the Differential Inductances - Graus, Johannes; Seilmeier, Markus; Hahn, Ingo; et al. (SLED, 2012)
A prerequisite for sensorless field oriented control of permanent magnet synchronous machines (PMSMs) at very low speed and standstill operation using signal injection methods is a sufficient saliency ratio of the differential inductances throughout the desired operating area. High frequency signal injection methods are very common in order to perform saliency tracking based sensorless operation. Vanishing saliency for certain operating points or a change of the sign of the difference of the differential inductances, which needs to be known for the sensorless algorithm, causes the loss of stability of the sensorless control method. A closed or partly closed stator slot geometry tends to show a local current dependent loss of the saliency even for low currents. This phenomenon typically shows up as a star-shaped pattern of the inductance surface as discussed further within this paper. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.influe_7
Keywords: Closed slots; differential inductances; permanent synchronous machine; sensorless position detection; standstill operation

Influence of Stator Saturation on the Differential Inductances of PM-Synchronous Machines with Concentrated Winding - Graus, Johannes; Hahn, Ingo; et al. (SLED 2012, 2012)
For sensorless position detection of permanent magnet synchronous machines at very low speed and standstill, signal injection methods are commonly used. As a prerequisite these so called saliency-tracking methods require a differential magnetic anisotropy of the machine, which is both position and load dependent and thus varying during operation. So the performance of sensorless operation strongly depends on the machine design. To investigate the influence of the stator saturation a machine model based on a magnetic equivalent circuit is presented in this document. This model is then used to analyze the differential inductances of a machine with concentrated windings. The results show that for some angles of the current vector the inductances do not vanish even for high currents. This phenomenon is explained by analyzing the flux paths. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.influe
Keywords: concentrated winding; cross saturation; differential magnetic anisotropy; magnetic equivalent circuit; permanent magnet synchronous machine; sensorless position detection

Modeling and Optimization of a Short-Circuited Rotor Winding of a PMSM for Saliency Tracking - Hahn, Ingo; Graus, Johannes (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
Sensorless position estimation based on signal-injection methods always requires a resistance- or inductance-based anisotropy. Therefore, a short-circuited electrical winding can be attached on the rotor. This paper proposes a simplified machine model by which the influence of one or more short-circuited rotor windings can be calculated and optimized with little effort. Simulations for the optimized rotor winding configurations are presented and compared to measurement results from an experimental machine. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.modell
Keywords: permanent magnet motors; ringed-pole; sensorless control; sensorless drives

Sensorless Capability of an Interior Permanent Magnet Synchronous Machine with a Short-Circuited Rotor Winding - Hahn, Ingo; Graus, Johannes (IECON, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.sensor_7